Correlation of spirometry and six minute walk test in patients with chronic obstructive pulmonary disease from Sundargarh, Odisha, India - Dinakar, Yara; Kiran, Pradeep Panchadi; Mohanty, Akshaya K.; Sahu, Praveen Kishore; Mohanty, Anita (International Journal of Research in Medical Sciences, 2019)
Background: Six‑Minute Walk Test (6MWT) is a simple, objective, reproducible test which correlated well with different spirometric indices, and thus able to predict severity of Chronic Obstructive Pulmonary Disease (COPD) and can replace spirometry in resource poor set‑up. Here, author evaluated the correlation of 6 minute walk distance (6MWD) with spirometric indices in COPD patients and the potential of 6MWT as an alternative to the assessment of severity of COPD. Methods: This cross-sectional observational study included a total of 80 COPD patients, diagnosed by GOLD criteria (Post bronchodilator FEV1/ FVC ratio <0.7). Modified Medical Research Council (mMRC) grading was used (age, weight, height, body mass index- BMI and breathlessness) and all the patients underwent spirometric measurement of FEV1, FVC and FEV1/ FVC ratio and tests were repeated after bronchodilation using 200-400 μg of salbutamol. 6MWT was performed following American Thoracic Society (ATS) protocol of 6MWT and distance was measured in meters. Results: Author found significant negative correlation of 6MWT with age (r=-0.384, p=0.00) and mMRC grading of dyspnea (r=-0.559, p=0.00) and significant positive correlation with height (r=0.267, p=0.019) and weight (r=0.293, p=0.008). Significant positive correlation of 6MWD was noted with post bronchodilator FEV1(r=0.608, p=0.00), FEV1% (r=0.429, p=0.00), FVC (r=0.514 p=0.00), FVC% (r=0.313 p=0.005), FEV1/FVC % (r=0.336, p=0.001). Positive correlation was also observed between 6MWT and BMI but statistically insignificant (r=0.177, p=0.116). There was significant negative correlation between 6MWT and GOLD staging (r=-0.536, p=0.00). Conclusions: This finding concludes that 6MWT can be used for the assessment of severity of disease in COPD patients in places where spirometry is not available.